Identification of Off-label Drug Prescription for Inpatient Pediatric Patients at Ciamis Regional Hospital - Puspitasari, Yusi (Ad-Dawaa : Journal of Pharmacy, 2024)
Rational and appropriately indicated drug administration to each patient is an effort to provide quality health services in hospitals and provide optimal therapy for patients. In reality, in some places there are drugs that are prescribed but do not comply with official drug information and do not comply with what is stated in the distribution permit, which are called off-label drugs. Drugs are categorized as off-label indications if the drugs used are outside the indications stated in the leaflet. The purpose of this study was to determine the description of off-label drug prescriptions for pediatric patients at General Hospitals in the Ciamis Region. Data collection on off-label drug prescriptions was carried out retrospectively, by taking inclusion and exclusion data, which were in accordance with the criteria for rational drug use. The sampling technique used was total sampling, namely taking data from medical records of inpatient pediatric patients from November to April. Data processing was carried out using descriptive analysis. The samples used were all prescriptions received that met the inclusion and exclusion criteria for pediatric patients. Of the 1,461 drug prescription samples obtained, no prescription of off-label indication drugs was found in pediatric patients. In other words, 100% of the samples were included in the list of drugs in the on-label indication category. From this study, it can be concluded that no prescription of off-label indication drugs was found in pediatric inpatients at Ciamis Regional Hospital.